Pengaruh Pengendalian Internal, Integritas, Asimetri Informasi dan Kapabilitas Pada Kecurangan Akuntansi - Nita, Ni Komang Norma; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2019)
This study aims to determine the effect of internal control, integrity, information asymmetry and capability on accounting fraud in OPD District X. The population used is 37 OPD. The sample in this study was the Head of the OPD, Secretary of the OPD, Financial Staff and Managers of each Service in District X with a total of 148 respondents. The method of determining the sample uses a purposive sampling method and data collection using a questionnaire. Data were analyzed using Linear Regression Analysis. Based on the results of the analysis show that internal control and integrity have a negative effect on accounting fraud. While the information asymmetry and capability variables have a positive effect on accounting fraud. For ODP District X in making decisions related to the existence of internal control, integrity, information asymmetry and capabilities in an organization so that this can affect the level of accounting fraud. Keywords : Internal control, integrity, information asymmetry, capability, accounting fraud.